The protective roles of augmenter of liver regeneration in hepatocytes in the non-alcoholic fatty liver disease - Dong, Yuan; Zhang, Yuejie; Feng, Yingmei; An, Wei (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) occurs in 25% of the global population and manifests as lipid deposition, hepatocyte injury, activation of Kupffer cells and stellate cells, and steatohepatitis. Predominantly expressed in hepatocytes, augmenter of liver regeneration (ALR) is a key factor in liver regulation that can alleviate fatty liver disease and protect the liver from abnormal liver lipid metabolism. ALR has three isoforms (15-, 21-, and 23-kDa), amongst which 23-kDa ALR is the most extensively studied. The 23-kDa ALR isoform is a sulfhydryl oxidase that resides primarily in the mitochondrial intermembrane space, whereby it protects the liver against various types of injury. In this review, we describe the role of ALR in the regulation of hepatocytes in the context of NAFLD. We also discuss questions about ALR that remain to be explored in the future. In conclusion, ALR appears to be a promising therapeutic target for the treatment of NAFLD.